Determinants of Stock Returns: The Role of Profitability, Valuation Ratios, and Firm Size in the Jakarta Islamic Index (2016–2020) - Yulianto Yulianto; Yusnita Octafilia (Research in Accounting Journal (RAJ), 2025)
This study aims to determine the effect of Return on Assets, Net Profit Margin, Price-Earnings Ratio, Earnings Per Share, and Company Size on the Jakarta Islamic Index Stock Return for the period 2016–2020. The object of this research is a company listed in the Jakarta Islamic Index from 2016 to 2020. The population in this study is 30 companies. The sampling technique used was Purposive Sampling, and a sample of 29 companies was obtained. The data analysis technique used was multiple linear regression, utilising SmartPLS 3.0, because the research data were not normally distributed when analysed in SPSS. The results of this study indicate that the variables of Return on Assets, Net Profit Margin, Price-Earnings Ratio, Earnings Per Share, and Company Size have no significant effect on the stock returns of the Jakarta Islamic Index for the period 2016–2020.